Impeachment of Regional Heads Resulted in Direct Election in the Perspective of Constitutional Law - Fakihudin, Rifki (Universitas Negeri Semarang, 2021)
This article examines the DPRD authority over the impeachment of regional heads resulting from direct elections. Impeachment is a proposal for dismissal by DPRD against regional heads. The impeachment mechanism emerged after the amendment of the UUD 1945 along with democratic elections. The impeachment process carried out by the DPRD is based on Law Number 9 of 2015 and Government Regulation Number 12 of 2018. This study uses qualitative legal research and a normative juridical approach that is associated with a developing case. The data sources used in this study are primary and secondary legal materials, with analysis using deductive qualitative techniques and aiming to collect information as study material. The authority of the DPRD as a regional institution has a supervisory function over the policies taken by the government, namely the regional head. Through the impeachment mechanism, regional heads can be dismissed if they commit a violation. This study provides an explanation of the ideal mechanism for impeachment of regional heads in the perspective of constitutional law.